The Effect of Treadmill Aerobic Exercise on Walking Distance, Lung Function and Quality of Life in Tuberculosis Patients - Muhamad Ilham; Marina Moeliono; Prayudi Santoso (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Objective: To observe the effect of treadmill aerobic exercise on walking distance, lung functionand QoL in lung tuberculosis patients.Methods: It was an interventional study using controlled random sampling with pre- and post- interventionobservation. The study took place at Hasan Sadikin Hospital, Bandung. Subjects were post-category IImedicationpulmonary TB patients with negative AFB conversion, males and females aged 18-60 years,normal BMI (according to Indonesian Ministry of Health 2003), able to comprehend spoken, writtenand signed instructions (mini mental state examination - MMSE 22-30), able to undergo a six-minuteswalking test (6MWT), cooperative and willing to participate in the study. This study analyzed data from30 subjects divided into two groups (interventional vs control group, each 15 subjects). Control groupwas given educational program, breathing techniques and chest- expansion exercises to do at home for6 weeks (3 times a week), whereas the study group received additional aerobic exercise for 6 weeks(walking on a treadmill, 3 times a week, 30-60 minutes per session) with the intensity of 80% of the speeddetermined from the result of the 6MWT. Pre- and post- six weeks, walking distance (6MWT), lungfunction and St. George’s Respiratory Questionnaire (SGRQ) evaluation were obtained from subjects.Results: Walking distance of interventional group (mean 75.53 m, p<0.05) increased significantly after6 weeks. There were also significant difference between two groups in the SGRQ components exceptfor symptoms. Lung functions as shown on FVC and FEV1 increased significantly in interventionalgroup. However, this increase was not confirmed by the change of breathing impairment pattern.Conclusion: The significant difference between the study and the control groups showed that aerobicexercise using treadmill gives better improvement on the quality of life. This fact demonstratesthat exercise program in pulmonary rehabilitation remains the core program to increase functionalcapacity and quality of life.Keywords: lung tuberculosis, aerobic exercise, treadmill, walking distance, quality of life, SGRQ